Computerised remote monitoring for low voltage harmonic measurement system / Ruslaan Abd. Ghani - Abd. Ghani, Ruslaan (1999)
This project involves the design and development of a computerised remote monitoring low voltage harmonic measurement system. The project is an improvement of a previous work which consists of remote data acquisition Unit (using PCL-818L data acquisition card), (RDAU), monitoring unit (MU) and hayes compatible modems as communication link. The improvements involve the development of new features for the Remote Harmonic Monitoring Software (RHMS), the sampling frequency for data acquisition software (DAS) and the hardware for transducer circuit. The RDAU and MU communicate through the Hayes compatible modem via telephone line. Sampling technique and fast fourier Transform (FFT) were used to compute system voltage and current for harmonic analysis. The software developed on visual basic is also able to determine the value of system powers and power factor. The new development system using ADAM-4550 radio modem modula is the alternative solution for the computerised remote monitoring system if the telephone line is not available.